Ética e teoria da justiça em John Rawls: a práxis humana naperspectiva democrática. - Santos Junior, José Antônio dos (2022)
The dissertation aims to research Ethics and Justice and their relations with equity, society, institutions, observing the principles of equality and freedom in a democratic perspective. John Rawls. The text was published in 1971, being a landmark in political philosophy and a reformulation of classical liberalism. Rawls presents us with categories such as the veil of ignorance, difference principle, original position, procedural justice, formal justice, distribution of consumer goods, capabilities, sense of justice, the role of authority, psychology in the moral sphere, debate and the role of institutions, society and individuals, among other issues It is intended to use the Rawlsian path and demonstrate the basis of the proposed social justice, using morality and a social contract formalized in consensus to support the democratic political proposal. The method used in the research will be supported by researchers who produce in-depth knowledge about the philosopher as well as the categories correlated to the theme and central argument of the dissertation. of justice, and understands them effective in the practical scope, where we arrive Human praxis in the democratic perspective, as conclusion of our work.